Public Art and Memory. Meaning Systems - Ricart Ulldemolins, Núria; Guixé Coromines, Jordi (Huarte de San Juan. Geografía e Historia, 2020)
«Re-signifying» memory spaces is an academic subject analysed by different disciplines: historiography, art, architecture, heritage, sociology, political science, etc. We propose an interdisciplinary perspective, specifically interested in the languages of art and the systems of meaning in public space. The methodology develops a blended approach, divided in two parts: the first one, analyses four conceptual perspectives focused on public space and meaning; the second one, tries to apply all the ideas in an experimental model.
Keywords: Public art; monument; memory; public space; «re-signifying»